Features of treatment of scoliosis of the 3rd degree in a patient with Down syndrome - Troshyna, Maria; Ovdiy , Maria (The Ukrainian Scientific Medical Youth Journal, 2025)
scoliosis is a common complication of Down syndrome, resulting from muscle hypotonia, ligamentous instability, and neuromuscular dysfunction. The course of grade III scoliosis is particularly difficult, negatively affecting physical activity, respiratory function, and quality of life of patients. The presented clinical case describes the effectiveness of Schrot therapy in combination with wearing a Chenault corset for one year in a 14-year-old patient with Down syndrome and grade III S-shaped scoliosis. The results showed a clinically significant decrease in Cobb angles, improvement in functional indicators, and general well-being.